PEMBERDAYAAN MASYARAKAT NELAYAN DI KECAMATAN TEMPURSARI KABUPATEN LUMAJANG - Irdiana, Sukma; Iristian, Jovi (IMPOWERMENT SOCIETY, 2019)
This study aims to determine the development and empowerment, obstacles in empowerment, the role of government in empowerment. This study used a descriptive qualitative research design using survey methods, field observations, interviews and triangulation. The subjects of the study were the fishermen of Tempursari Subdistrict, Lumajang Regency with 70 fishermen. The results showed that: (1) the process of community development and empowerment included (a) increased skills and independence of the fishing community, (b) there were social, economic, and educational impacts, (2) inhibiting factors including the character or nature and thinking of the community different, constrained human resource readiness, community understanding is still low. (3) the role of government that is with the participation and involvement in community empowerment. (4) Strategies in developing the coastal zone, namely the community economy.